Assessment of some nutrient contents and enzyme activity in early germinating bean of two soybean varieties (Glycine max) DT84 and DT2008 - Thuy, Tran Thi; Thu Hoai, Nguyen Thi; Mo, Tong Thi (Academia Journal of Biology, 2018)
Soybeans have become widly important and popular due to a high demand of plant protein and fiber. Besides, grains of soybean contain abundance of vitamines, minerals and bioactive compounds such as isoflavone, gama- aminobutyric acid... However, some antinutrient compounds such as tripsin inhibitor and phytate are available in these grains. In this paper, nutrient compounds (protein, lipid, polysaccharide and dissolved minerals) and enzymes of early germinating seeds of soybean varieties (DT84 and DT2008) were evaluated and compared to those of non-germinating beans in order to determine a suitable germinating period for food processing. Experimental results showed that: Activities of enzymes (protease, amylase and phytase) in early germinating soybeans were higher than those in dry beans. Those enzymes have made major changes in nutrient compounds of soybeans: proteins, polysaccharides and lipids reduced. Especially, the content of phytate, an antinutrient factor, reduced signicantly (17.0-48.9% in DT84 variety and 28.0-60.7% in DT2008 variety) during early germinating period of soybeans. However, easy uptake minerals (calcium, iron and zinc ions), reduced sugars and peptides were significantly increased. In detail, the increase in dissolve iron cation was 10.31-12.13%, calcium cation was 31.56-35.75% and zinc cation was 31.38-43.32%. These results confirmed the positive effect of germinating soybeans in food processing.